Reverse Logistics Network Optimization of Express Packaging Boxes in Colleges and Universities Based on The Background of Green Logistics - Zhang, Ying (International Journal of Computer Science and Information Technology, 2024)
Given the high volume of express delivery in universities and the inadequate recycling system for express packaging boxes, this paper studies a reverse logistics network for express packaging boxes based on green logistics. Green logistics mainly refers to the sustainable development model of express delivery aimed at reducing resource consumption and environmental pollution during the logistics process. This paper constructs a reverse logistics optimization model for express packaging boxes, aiming to minimize the total cost of reverse logistics by recycling express packaging to reduce environmental pollution while maximizing social benefits. At the same time, triangular fuzzy numbers were used to define the uncertainty parameters in the text, and feasibility theory was used to equivalently transform the constraint conditions of the model by setting parameters such as confidence levels. The experimental results indicate that the model can realistically simulate the decision-making process of reverse logistics network for university express delivery packaging boxes, and is feasible; The Lingo program can effectively assist in finding the best solution.